Ohmic contacts to Hall sensors based on n-InSb-GaAs(i) heterostructures - Boltovets, N.S.; Konakova, R.V.; Kudryk, Ya.Ya.; Milenin, V.V.; Mitin, V.F.; Mitin, E.V.; Lytvyn, O.S.; Kapitanchuk, L.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
We consider ohmic contacts to the n-InSb epitaxial layers grown on a semi-insulating GaAs substrate. The ohmic contacts are formed through titanium metallization with subsequent gilding. Using the structural (AFM and XRD) and analytical (AES) techniques, we showed that thermal annealings at Т = 300 °С (for 60 s) and 360 °С (for 30 s) do not change the phase composition of the metallization. This ensures thermal stability of the contacts and Hall sensors made on the basis of Au–Ti–n-InSb–GaAs(i) structures.